A sintering method of high-performance piezoelectric ceramics based on shrinkage characteristics for regulating oxygen partial pressure
Patent Information
- Application Number
- CN202611278840.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-27
AI Technical Summary
然而,热压烧结设备复杂、成本高昂,且还原性气氛易引起B位离子变价;掺杂改性虽可改善部分性能,但往往以降低居里温度为代价,限制了高温应用
(1)通氧烧结有效抑制了PbO的高温挥发,避免了组分偏离化学计量,有利于保持PZT的相结构和电学性能;(2)氧扩散传质的增强促进了闭气孔的消除,实现了致密度的显著提升,进而增强了陶瓷的力学可靠性;(3)该方法不改变材料组分,因此不牺牲居里温度,克服了传统掺杂改性中压电性能提升伴随居里温度下降的固有矛盾;(4)通过在坯体收缩起始阶段引入氧气,确保了氧气在气孔封闭前充分进入坯体内部,实现了气氛调控效率的最大化;(5)在压电陶瓷生坯制备过程中结合冷等静压成型处理,提高了生坯的均匀性和密度,为后续氧分压烧结提供了更优的初始条件,进一步保障了烧结体的性能一致性。
Smart Images

Figure CN122977855A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of piezoelectric ceramic material preparation technology, and relates to a sintering method for high-performance piezoelectric ceramics based on shrinkage characteristics to regulate oxygen partial pressure. It is applicable to piezoelectric ceramic devices used under high temperature, high frequency and high reliability conditions. Background Technology
[0002] Piezoelectric ceramic materials, such as lead zirconate titanate (Pb(Zr,Ti)3, PZT)-based, bismuth-based perovskites (such as BSPT), and bismuth layered ferroelectrics (such as BIT), are widely used in high-temperature sensors, actuators, and energy conversion devices due to their excellent electromechanical coupling properties. With the development of high-end applications such as aerospace, deep well exploration, and nuclear energy, comprehensive and stringent requirements have been placed on the Curie temperature, piezoelectric activity, and long-term service reliability of piezoelectric ceramics.
[0003] Taking the application of PZT piezoelectric ceramic tubes in microfluidics and droplet jetting as an example, their service conditions are often extremely harsh: they need to withstand high-frequency driving (>50 kHz) and high-temperature operating environments, while requiring the devices to have a large aspect ratio and thin-walled microstructure. This poses a comprehensive challenge to the piezoelectric activity, temperature stability, and mechanical reliability of piezoelectric ceramic materials.
[0004] Taking bismuth-based perovskite piezoelectric ceramic Bi(Sc,Ti)O3-PbTiO3 (BSPT) as an example, this system is considered an ideal material for high-temperature piezoelectric sensing due to its high Curie temperature (>400 °C). However, BSPT ceramics face a severe densification problem during sintering: Bi has an extremely high vapor pressure at high temperatures, and its volatilization is more intense than that of PbO, leading to the generation of a large number of bismuth and oxygen vacancies, which severely hinders grain boundary migration and mass transport. Under conventional air sintering, the relative density of BSPT is usually difficult to exceed 94%. Insufficient density results in low flexural strength, which cannot meet the reliability requirements under thermal shock conditions; at the same time, the movement of domain walls is pinned by pores and defect dipoles, leading to a decrease in the piezoelectric coefficient. d 33 The value was lower than the theoretical value, which limited the high-temperature application of this system.
[0005] Taking bismuth-based piezoelectric ceramics as an example, although they have a high Curie temperature under high-temperature service conditions, bismuth is prone to volatilization at high temperatures, leading to the generation of oxygen vacancies and defect dipole pinning, which severely degrades the piezoelectric performance. Piezoelectric ceramics prepared by traditional air sintering methods generally suffer from insufficient density (usually <96%) and low mechanical strength, which cannot meet the reliability requirements under high stress or thermal cycling conditions.
[0006] In existing technologies, hot pressing sintering or doping modification are commonly used to improve density. However, hot pressing sintering equipment is complex and expensive, and the reducing atmosphere can easily cause valence changes in B-site ions. While doping modification can improve some properties, it often comes at the cost of lowering the Curie temperature, limiting its application at high temperatures. Oxygen-permeable sintering has been shown to effectively suppress the volatilization of volatile components and promote densification, but existing research is mostly focused on specific systems, lacking a universal oxygen partial pressure control strategy based on sintering physics that can be applied across systems.
[0007] Therefore, developing a sintering method that does not change the material composition, has strong universality, and can precisely control the oxygen partial pressure by combining the shrinkage characteristics of the green body during sintering is of great engineering value and industrial significance for improving the comprehensive performance of various piezoelectric ceramics. Summary of the Invention
[0008] In view of the aforementioned problems in the prior art, the purpose of this invention is to provide a sintering method for high-performance piezoelectric ceramics based on oxygen partial pressure control according to shrinkage characteristics. This method is a general sintering method that uses the shrinkage characteristics of the green body to control the oxygen partial pressure of the sintering atmosphere to achieve synergistic optimization of the densification and electrical properties of piezoelectric ceramics. This invention effectively suppresses the volatilization of volatile components (such as PbO and Bi2O3) by precisely controlling the oxygen partial pressure and oxygen-inducing temperature range during the sintering process, combined with the inherent shrinkage characteristics of the green body during sintering. This significantly improves the density and mechanical reliability of the ceramic, while maintaining the original high Curie temperature of the material and enhancing its piezoelectric properties.
[0009] On one hand, the present invention provides a sintering method for high-performance piezoelectric ceramics based on the control of oxygen partial pressure by shrinkage characteristics, comprising the following steps: (1) Place the piezoelectric ceramic green body in a sintering furnace and heat it from room temperature to the oxygen initiation temperature at the first heating rate; (2) At the oxygen initiation temperature, high-purity oxygen is introduced into the sintering furnace, and the oxygen partial pressure in the furnace is controlled to the first oxygen partial pressure. The furnace is kept warm for the first preset time to allow the oxygen to fully diffuse and penetrate into the green body. After the heat preservation is completed, the oxygen supply is stopped and the gas inlet valve is closed. (3) Continue heating at the second heating rate to the sintering temperature and hold for the second preset time to make the green billet densify and sinter; during this process, as the temperature inside the furnace continues to rise, the gas inside the furnace expands due to heat and the pressure naturally rises, and the first oxygen partial pressure is maintained by controlling the flow rate at the gas outlet of the sintering furnace. (4) After the heat preservation in step (3) is completed, the furnace is cooled to room temperature to obtain the high-performance piezoelectric ceramic.
[0010] Preferably, in step (1), the piezoelectric ceramic is selected from Pb(Zr,Ti)O3-based piezoelectric ceramics (PZT), bismuth-based perovskite (BSPT)-based piezoelectric ceramics or bismuth layered structure (BLSF) piezoelectric ceramics; The preparation method of the piezoelectric ceramic green body includes: weighing raw materials according to the stoichiometric ratio of piezoelectric ceramics, mixing them by planetary ball milling, drying them, sieving them, and then pre-firing them to synthesize piezoelectric ceramic powder; after the piezoelectric ceramic powder is ball-milled and granulated twice, it is first molded and then subjected to cold isostatic pressing to obtain the uniform and dense piezoelectric ceramic green body; preferably, the pressure of the cold isostatic pressing is 150-300 MPa, and the holding time is 1-10 minutes.
[0011] Preferably, in step (1), the first heating rate is 2 to 5 °C / min.
[0012] Preferably, in step (1), the oxygen initiation temperature is determined by the following method: performing a shrinkage curve test on the piezoelectric ceramic green body to obtain the shrinkage rate curve of the green body during the heating process, and taking the temperature corresponding to the start of shrinkage as the oxygen initiation temperature; preferably, the oxygen initiation temperature is 600-850 ℃.
[0013] Preferably, in step (2), the purity of the high-purity oxygen is ≥90%, and more preferably ≥99%; The pressure of the first oxygen partial pressure is 1.2 to 2 atmospheres; The first preset time is 0.5 to 1 hour.
[0014] Preferably, in step (3), the second heating rate is 1 to 2 °C / min; The sintering temperature is 1100–1280 °C; Preferably, when the piezoelectric ceramic is a PZT system, the sintering temperature is 1200–1280 °C; Preferably, when the piezoelectric ceramic is a BSPT system, the sintering temperature is 1150–1250 °C; Preferably, when the piezoelectric ceramic is a BLSF system, the sintering temperature is 1100–1200 °C.
[0015] Preferably, in step (3), the second preset time is 1 to 4 hours.
[0016] Preferably, in step (4), the cooling rate is 2 to 5 °C / min.
[0017] On the other hand, the present invention provides a high-performance piezoelectric ceramic prepared according to the above-described sintering method.
[0018] Preferably, the relative density of the high-performance piezoelectric ceramic is ≥98%; The high-performance piezoelectric ceramic has a piezoelectric coefficient d. 33 It improves upon traditional air sintering by more than 6%; When the piezoelectric ceramic is a PZT system, the Curie temperature is ~360 ℃; When the piezoelectric ceramic is a BSPT system, the Curie temperature is ~450 ℃; When the piezoelectric ceramic is a BLSF system, the Curie temperature is ~650 ℃. Beneficial effects
[0019] By controlling the oxygen partial pressure during the sintering process, this invention achieves at least the following beneficial effects: (1) Oxygen sintering effectively suppresses the high-temperature volatilization of PbO, avoids the composition from deviating from stoichiometry, and is conducive to maintaining the phase structure and electrical properties of PZT; (2) Enhanced oxygen diffusion mass transfer promotes the elimination of closed pores, achieves a significant increase in density, and thus enhances the mechanical reliability of ceramics; (3) This method does not change the material composition, so it does not sacrifice the Curie temperature, and overcomes the inherent contradiction of the improvement of piezoelectric performance accompanied by the decrease of Curie temperature in traditional doping modification; (4) By introducing oxygen at the beginning stage of green body shrinkage, it is ensured that oxygen fully enters the interior of the green body before the pores are closed, thus maximizing the efficiency of atmosphere control; (5) Combining cold isostatic pressing with the preparation of piezoelectric ceramic green body improves the uniformity and density of the green body, provides better initial conditions for subsequent oxygen partial pressure sintering, and further ensures the performance consistency of the sintered body. Attached Figure Description
[0020] Figure 1 The XRD diffraction patterns of oxygen partial pressure sintered PZT ceramics and conventional air sintered PZT ceramics in Example 1 of the present invention are compared; where (a) is a comparison of XRD diffraction patterns and (b) is a refined Rietveld structure diagram. Figure 2 The images show a comparison of the cross-sectional morphology of oxygen partial pressure sintered and conventional air-sintered PZT ceramics in Example 1 of this invention, with (a) showing the cross-sectional morphology of the air-sintered sample and (b) showing the cross-sectional morphology of the oxygen partial pressure sintered sample. Figure 3 The shrinkage curve and shrinkage rate curve of the PZT green body during the sintering process of this invention are shown. Figure 4 A comparison of the dielectric temperature spectra of PZT ceramics sintered by oxygen partial pressure and conventionally air-sintered in Example 1 of this invention; Figure 5 The shrinkage curve and shrinkage rate curve of the BSPT green body during the sintering process in Example 3 of the present invention; Figure 6 Scanning electron microscope cross-sectional morphology of the Nb-PZT-based piezoelectric ceramic prepared in Comparative Example 1; Figure 7 Scanning electron microscope (SEM) cross-sectional morphology of the Nb-PZT-based piezoelectric ceramic prepared for Comparative Example 2. Detailed Implementation
[0021] To further illustrate the invention's content, features, and practical effects, the invention will be described in detail below with reference to embodiments. It should be noted that the modification methods of the invention are not limited to these specific implementation methods. Equivalent substitutions and modifications made by those skilled in the art based on their reading of the invention's content, without departing from the spirit and essence of the invention, are also within the scope of protection claimed by this invention.
[0022] First, this invention provides a sintering method for high-performance piezoelectric ceramics based on oxygen partial pressure regulation using shrinkage characteristics. By precisely controlling the oxygen partial pressure and oxygen-inlet temperature range during the sintering process, and combining this with the inherent shrinkage characteristics of the green body during sintering, the volatilization of volatile components (such as PbO and Bi2O3) is effectively suppressed, significantly improving the ceramic density and mechanical reliability. While improving the piezoelectric properties, the original high Curie temperature of the material is maintained.
[0023] Specifically, this invention introduces high-purity oxygen at the moment when the green body begins to shrink significantly (i.e., the shrinkage initiation temperature). The core logic is that, in the initial shrinkage stage, although the green body already possesses certain sintering necks and intergranular connections, the open pore network remains unobstructed. At this time, the introduced oxygen can rapidly diffuse and permeate throughout the green body through the unclosed interconnected pores, achieving equilibrium between the oxygen partial pressure within the green body's pores and the high-oxygen atmosphere in the furnace. As the temperature continues to rise and the green body further shrinks into the middle and later stages of sintering, the open pores gradually close into isolated closed pores. At this point, the oxygen partial pressure within the pores is in a high-oxygen state, providing a sufficient internal oxygen source for the subsequent high-temperature densification stage. This strategy avoids both the low oxygen utilization rate and uneven shrinkage caused by introducing oxygen too early (at low temperatures) and the inability of oxygen to enter the green body due to introducing oxygen too late (after the formation of closed pores). Based on this oxygen-inducing strategy, a high oxygen partial pressure is introduced at the beginning of the shrinkage stage, which suppresses the significant volatilization of PbO / Bi2O3 in the temperature range where it begins to intensify. This keeps the decomposition reaction of volatile components suppressed throughout the subsequent high-temperature sintering process, avoiding A-site vacancies and associated oxygen vacancies caused by the lack of volatile components. Consequently, the grain boundary structure is more complete, and the mechanical reliability is improved. In addition, the reduction of oxygen vacancies: (1) eliminates domain wall pinning sources, making it easier for domain walls to flip and move under an external electric field, significantly improving the piezoelectric coefficient and dielectric constant; (2) reduces carrier concentration and leakage current, improving the resistivity and breakdown field strength of the material; (3) avoids fatigue aging caused by oxygen vacancy migration, enhancing the reliability of piezoelectric ceramics under high-frequency, high-field cycling. On the other hand, the introduction of a high oxygen partial pressure at the beginning of the shrinkage stage increases the chemical potential of lattice oxygen, accelerates the diffusion rate of oxygen along grain boundaries and bulk phase, and makes it easier for oxygen molecules in the pores to be discharged, thereby improving the density of the ceramic. In addition, oxygen partial pressure sintering does not change the phase structure of the material, so it can still maintain the original high Curie temperature of the material.
[0024] The following exemplarily illustrates the sintering method of high-performance piezoelectric ceramics based on oxygen partial pressure regulation by shrinkage characteristics provided by the present invention.
[0025] Piezoelectric ceramic green bodies were prepared using a solid-state method. Raw materials were weighed according to the stoichiometric ratio of piezoelectric ceramics, mixed by planetary ball milling, dried, and sieved, then pre-fired to synthesize piezoelectric ceramic powder. The piezoelectric ceramic powder was then subjected to secondary ball milling and granulation, followed by molding to obtain a preliminary green body, and then cold isostatic pressing to obtain the piezoelectric ceramic green body. Subsequently, a descaling process was performed to fully remove granulating agents and organic binders.
[0026] In optional embodiments, piezoelectric ceramics include, but are not limited to, Pb(Zr,Ti)O3-based piezoelectric ceramics (PZT), bismuth-based perovskite (BSPT)-based piezoelectric ceramics, or bismuth layered structure (BLSF) piezoelectric ceramics.
[0027] In an optional embodiment, the pre-firing temperature is 800–1000°C, and the holding time is 2–5 hours. The cold isostatic pressing pressure is 150–300 MPa, and the holding time is 1–10 minutes. Cold isostatic pressing effectively eliminates the density gradient generated during molding, improves the uniformity of the green body, and lays the foundation for subsequent uniform sintering. The descaling temperature is 700–800°C, and the holding time is 2–4 hours; preferably, the heating rate is 0.5–2°C / min.
[0028] The piezoelectric ceramic green body is placed in a sintering furnace and heated from room temperature to the oxygen initiation temperature at a first heating rate.
[0029] In an optional embodiment, the first heating rate is 2 to 5 °C / min.
[0030] In an optional embodiment, the oxygen initiation temperature is determined by: performing a shrinkage curve test on the piezoelectric ceramic green body to obtain the shrinkage rate curve of the green body during the heating process, and taking the temperature corresponding to the start of shrinkage as the oxygen initiation temperature; preferably, the oxygen initiation temperature is 600-850 °C. This invention sets the temperature based on the peak shrinkage rate temperature or the inflection point temperature of the shrinkage rate to ensure that oxygen is introduced before a large number of closed pores form in the green body, allowing the oxygen to fully diffuse into the interior of the green body. Its function is that this temperature is the critical point at which the green body transitions from predominantly open pores to the formation of closed pores. Introducing oxygen at this temperature point allows high-purity oxygen to fully diffuse into the interior of the green body through the open pore network during the final window period before a large number of closed pores form, ensuring that oxygen has uniformly penetrated into each pore before the pores close, thereby achieving efficient synergy between atmosphere control and densification processes. If the oxygen initiation temperature is too low, the sintering neck of the green body has not yet formed, and the oxygen diffusion driving force is insufficient, resulting in low oxygen utilization. Microcracks may be introduced due to uneven shrinkage of the surface and interior. If the oxygen initiation temperature is too high, a large number of open pores will be closed, and external oxygen cannot enter the interior of the green body. The oxygen partial pressure in the closed pores will be locked in a low oxygen state, which cannot effectively promote the elimination of pores and inhibit the volatilization of volatile components. The effect of density improvement and piezoelectric performance improvement will be significantly weakened.
[0031] At the initial oxygen supply temperature, high-purity oxygen is introduced into the sintering furnace, and the oxygen partial pressure inside the furnace is controlled to the first oxygen partial pressure. The furnace is kept warm for a first preset time to allow the oxygen to fully diffuse and penetrate into the interior of the green body. After the warming is completed, the oxygen supply is stopped and the inlet valve is closed.
[0032] In an optional embodiment, the purity of the high-purity oxygen is ≥90%, preferably ≥99%. The pressure of the first oxygen partial pressure is 1.2 to 2 atmospheres; the first preset time is 0.5 to 1 hour. If the pressure of the first oxygen partial pressure is too low (e.g., below 1.2 atmospheres), the oxidation potential is insufficient to effectively suppress the volatilization of PbO or Bi2O3, the composition deviates from stoichiometry, resulting in defect dipole pinning domain walls, and insufficient pressure within the closed pores, thus limiting the density improvement effect. If the pressure of the first oxygen partial pressure is too high (e.g., exceeding 2 atmospheres), the requirements for equipment sealing and pressure resistance are stringent, increasing the preparation cost, and it may induce excessive oxidation of B-site ions or the formation of amorphous lead-rich phases at grain boundaries, which may degrade the piezoelectric properties. Excessive pressure difference may also cause cracking of the billet due to internal and external pressure imbalance. Therefore, the first oxygen partial pressure is preferably 1.2 to 2 atmospheres.
[0033] The green body is heated to the sintering temperature at a second heating rate and held for a second preset time to allow it to undergo densification sintering. During this process, as the temperature inside the furnace continues to rise, the gas inside the furnace expands due to heat, causing the pressure to rise naturally. The first oxygen partial pressure is maintained by controlling the flow rate at the gas outlet of the sintering furnace. After the holding period, the green body is cooled to room temperature with the furnace to obtain the high-performance piezoelectric ceramic.
[0034] In an optional embodiment, the second heating rate is 1–2 °C / min. The second preset time is 1–4 h. The sintering temperature is 1100–1280 °C; adjusted according to the ceramic system: when the piezoelectric ceramic is a PZT system, the sintering temperature is 1200–1280 °C; when the piezoelectric ceramic is a BSPT system, the sintering temperature is 1150–1250 °C; when the piezoelectric ceramic is a BLSF system, the sintering temperature is 1100–1200 °C. In this invention, oxygen is briefly introduced at the initial oxygen induction temperature and held at that temperature before oxygen supply is stopped. During the subsequent heating and sintering holding stages, the gas inside the furnace naturally expands and pressurizes as the temperature rises, and the furnace pressure is maintained stable only by controlling the flow rate at the furnace outlet. The mechanism of this design is as follows: oxygen diffuses and permeates sufficiently into the interior of the billet before the open pores close; when the closed pores form, the oxygen partial pressure inside the pores is locked at a high oxygen level, eliminating the need for continuous external oxygen supply; simultaneously, it avoids disturbing the furnace temperature uniformity by continuously introducing room temperature oxygen during the high-temperature stage, which is beneficial for uniform shrinkage and densification of the billet; maintaining constant high pressure through outlet flow rate control ensures that the volatilization balance of PbO (or Bi2O3) is continuously suppressed during the high-temperature stage, and the closed pores are more unstable under high pressure and are more easily eliminated through grain boundary diffusion, maintaining a low oxygen vacancy concentration, thereby achieving synergistic optimization of density and electrical properties. After the heat treatment is completed, pressure control is stopped, and the furnace cools to room temperature.
[0035] In an optional embodiment, the cooling rate is 2 to 5 °C / min.
[0036] In this invention, parameters such as the oxygen initiation temperature, sintering temperature, oxygen partial pressure, and holding time can be optimized and adjusted within the aforementioned range for PZT ceramics with different compositions or green bodies of different sizes. For example, for PZT systems with added sintering aids, the sintering temperature can be correspondingly reduced, and the oxygen initiation temperature range should also be adjusted accordingly. Furthermore, the sintering method provided by this invention can be combined with doping modification, such as using doping with elements like Mn, La, and Nb, to further optimize the overall performance under oxygen partial pressure sintering conditions.
[0037] In this invention, PZT ceramics sintered by oxygen partial pressure sintering and those sintered by air were compared and characterized, mainly including the following testing methods: X-ray diffraction analysis: phase analysis was performed using a PANalytical X-ray diffractometer; microstructure observation: cross-sectional morphology was observed using a field emission scanning electron microscope; dielectric property testing: the change of dielectric constant with temperature was measured using an impedance analyzer; density testing: the volume density was measured using the Archimedes' displacement method, and the relative density was calculated based on the theoretical density; piezoelectric property testing: a quasi-static method was used. d 33 The piezoelectric coefficient was measured by a measuring instrument, and the sample was polarized in silicone oil at 120 °C. Mechanical properties were tested: flexural strength, elastic modulus and compressive strength were tested using a universal testing machine; hardness was tested using the Vickers indentation method.
[0038] The high-performance PZT-based piezoelectric ceramics prepared by the above sintering method have a relative density ≥98%, preferably 98.5%; the piezoelectric coefficient of the PZT-based piezoelectric ceramics is... d 33 The PZT-based piezoelectric ceramic has a curie temperature of ~360 °C, a Vickers hardness of ≥2.85 GPa, preferably 2.92 GPa, and a compressive strength of ≥540 MPa, preferably 558 MPa.
[0039] The PZT-based piezoelectric ceramics prepared by the method of this invention exhibit a higher relative density (98.43%) than those prepared by conventional air sintering, compared to those prepared by conventional air sintering. The piezoelectric coefficient dp is also increased. 33 The Curie temperature was increased from 450 pC / N to 510 pC / N (an increase of 13%), the Vickers hardness increased from 2.68 GPa to 2.92 GPa, the compressive strength increased from 524 MPa to 558 MPa, and the Curie temperature was maintained at around 360 °C.
[0040] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below. Example 1
[0041] The sintering method for preparing high-performance Nb-doped Pb(Zr,Ti)O3 (Nb-PZT)-based piezoelectric ceramics based on oxygen partial pressure regulation using shrinkage characteristics in Example 1 includes the following steps: (1) Nb-doped Pb(Zr,Ti)O3 (Nb-PZT) based piezoelectric ceramic green bodies were prepared by solid-state method. PbO, ZrO2, TiO2 and Nb2O5 were used as raw materials. The raw materials were weighed according to the stoichiometric ratio of Nb-doped Pb(Zr,Ti)O3 (Nb-PZT) based piezoelectric ceramics. After mixing by planetary ball milling, drying and sieving, Nb-PZT powder was synthesized by pre-firing at 850℃ for 2 hours. The Nb-PZT powder was ball-milled and granulated twice. The green body was first molded to obtain a green body, and then cold isostatic pressing was performed to obtain Nb-PZT green bodies. The pressure of cold isostatic pressing was 200 MPa and the holding time was 10 minutes. Then, the temperature was raised to 750℃ at a heating rate of 2℃ / min in air atmosphere and held for 2 hours to remove the granulating agent and organic binder. (2) The obtained Nb-PZT green compact is placed in an alumina crucible and then placed in a controlled atmosphere sintering furnace. The temperature is increased from room temperature to 800 ℃ (oxygen initiation temperature) at a heating rate of 2 ℃ / min. This temperature is determined based on the shrinkage rate curve of the Nb-PZT green compact (e.g., Figure 3 As shown in the figure), when the temperature reaches 800℃, high-purity oxygen (purity ≥99.999%) is introduced into the furnace, and the pressure inside the furnace is maintained at 1.5 atmospheres (absolute pressure) through the pressure control system. Under this condition, the furnace is held for 0.5 hours to allow the oxygen to fully diffuse and penetrate into the interior of the green body. After the holding period, the oxygen supply is stopped and the gas inlet valve is closed. Then, the furnace is heated to 1260℃ at a heating rate of 2℃ / min and held for 2 hours for densification sintering. During this process, as the temperature continues to rise, the gas inside the furnace expands due to heat, causing the pressure to rise naturally. The pressure inside the furnace is maintained at 1.5 atmospheres by controlling the flow rate at the gas outlet of the sintering furnace. After the holding period, the furnace is allowed to cool naturally to room temperature to obtain high-performance Nb-PZT-based piezoelectric ceramics.
[0042] In this example, the relative density of the PZT ceramic sintered under oxygen partial pressure significantly increased from 95.37% to 98.43%; the remanent polarization increased from 54.41 μC / cm². 2 Increased to 60.23 μC / cm 2 The coercive field is slightly reduced, and the leakage current is significantly reduced. d 33 The dielectric loss was increased from 2.0% to 1.5%, the Vickers hardness increased from 2.68 GPa to 2.92 GPa, the elastic modulus increased from 17.8 GPa to 21.2 GPa, and the compressive strength increased from 524 MPa to 558 MPa.
[0043] Figure 1This is a comparison of the XRD diffraction patterns of PZT ceramics sintered by oxygen partial pressure sintering and those sintered by conventional air sintering in Example 1 of this invention. As shown in the figure, oxygen partial pressure sintering did not change the perovskite phase structure of the PZT ceramics, but the tetragonal distortion (c / a ratio) was slightly reduced, indicating an improvement in lattice order.
[0044] Figure 2 This is a comparison of the cross-sectional morphology of oxygen partial pressure sintered and conventional air-sintered PZT ceramics in Example 1 of this invention using scanning electron microscopy (SEM). As shown in the figure, the air-sintered sample has a large number of residual pores in its cross-section, while the oxygen partial pressure sintered sample has a dense cross-section with significantly reduced pores and exhibits transgranular fracture characteristics, indicating enhanced grain boundary bonding strength.
[0045] Figure 3 This figure shows the shrinkage curve and shrinkage rate curve of the PZT green body during the sintering process of this invention. As can be seen from the figure, the PZT green body exhibits significant shrinkage behavior during sintering, with the measured starting temperature being approximately 810℃. In this embodiment 1, the oxygen initiation temperature is set at 800℃, which basically coincides with the peak shrinkage rate. At this temperature, the green body has not yet formed a large number of closed pores, and is still mainly composed of open pores. Introducing oxygen allows it to diffuse sufficiently into the interior of the green body at the pore-closing front, enabling the oxygen partial pressure in the pores inside the green body to reach equilibrium with the furnace atmosphere. The design of holding at 800℃ for 0.5 hours further ensures sufficient oxygen penetration, providing a sufficient oxygen source for the subsequent high-temperature densification stage. Simultaneously, this temperature range is also the starting point for significant PbO volatilization. According to the PbO decomposition equilibrium, increasing the oxygen partial pressure can shift the equilibrium to the left, effectively inhibiting the decomposition and volatilization of PbO.
[0046] Figure 4 This figure compares the dielectric temperature spectra of oxygen partial pressure sintered PZT ceramics and conventional air-sintered PZT ceramics in Example 1 of this invention. As shown in the figure, the Curie temperature of the oxygen partial pressure sintered sample is basically the same as that of the air-sintered sample (~360℃), and the dielectric constant is increased throughout the entire test temperature range. This indicates that oxygen partial pressure sintering does not change the composition and phase structure of the material, thus maintaining the Curie temperature at 360℃, breaking the inherent contradiction in traditional doping modification where improved piezoelectric properties are accompanied by a decrease in Curie temperature.
[0047] Table 1 lists a performance comparison of Nb-PZT piezoelectric ceramics sintered by oxygen partial pressure sintering and those sintered by air sintering.
[0048] Table 1: .
[0049] As shown in Table 1, the Nb-PZT piezoelectric ceramic sintered by oxygen partial pressure of this invention exhibits significantly improved overall performance compared to the traditional air-sintered sample: piezoelectric coefficient d 33The electromechanical coupling coefficient was increased from 450 pC / N to 510 pC / N, representing a 13.3% improvement. k p and k t The values were increased from 0.66 and 0.62 to 0.69 and 0.65 respectively, indicating that the piezoelectric activity was comprehensively optimized; the remanent polarization intensity... P r The coercive field increased significantly from 54.41 μC / cm² to 60.23 μC / cm², an increase of approximately 10.7%, while the coercive field... E C The slight decrease (from 11.0 kV / cm to 10.8 kV / cm) reflects a weakening of the domain wall pinning effect and greater freedom of domain wall movement, which is closely related to the decrease in oxygen vacancy concentration and the effective elimination of defect dipole pinning; Curie temperature T C The temperature remained stable at 360 °C, demonstrating that oxygen partial pressure sintering did not alter the material composition and phase structure, successfully overcoming the technical contradiction of decreased Curie temperature accompanying improved piezoelectric performance in traditional doping modifications. It is evident that this invention achieves synergistic optimization among piezoelectric activity, ferroelectric properties, and thermal stability by precisely introducing high oxygen partial pressure at the shrinkage peak temperature. Example 2
[0050] In Example 2, high-performance Nb-doped PbO-based Nb-PZT piezoelectric ceramics (chemical composition: Pb) were prepared by controlling oxygen partial pressure based on shrinkage characteristics. 1.03 (Zr 0.52 Ti 0.48 ) 0.98 Nb 0.02 The sintering method for O3 includes the following steps: (1) Nb-doped Pb(Zr,Ti)O3 (Nb-PZT) based piezoelectric ceramic green bodies were prepared by solid-state method. Using PbO, ZrO2, TiO2, and Nb2O5 as raw materials, the raw materials were weighed according to the stoichiometric ratio of Nb-doped Pb(Zr,Ti)O3 (Nb-PZT) based piezoelectric ceramics. After mixing by planetary ball milling, drying, and sieving, Nb-PZT piezoelectric ceramic powder with an excess of 3 wt% PbO was synthesized by pre-calcination at 850℃ for 2 hours. The Nb-PZT piezoelectric ceramic powder was then subjected to secondary ball milling and granulation, and firstly, it was molded to obtain a preliminary green body, and then subjected to cold isostatic pressing to obtain a PZT green body. The cold isostatic pressing pressure was 200 MPa, and the holding time was 10 minutes. Subsequently, the temperature was raised to 750℃ at a heating rate of 2℃ / min and held for 2 hours in air atmosphere for de-plasticization treatment to fully remove granulating agents and organic binders. (2) The obtained Nb-PZT green compact is placed in an alumina crucible and then placed in a controlled atmosphere sintering furnace. The temperature is increased from room temperature to 800 ℃ (oxygen initiation temperature) at a heating rate of 2 ℃ / min. This temperature is determined based on the shrinkage curve of the Nb-PZT green compact (e.g., Figure 3 As shown in the figure, since Example 2 and Example 1 both belong to the Nb-PZT system, their green shrinkage characteristics are basically the same. Therefore, Example 2 adopts the same oxygen initiation temperature (800℃) as Example 1. When the temperature reaches 800℃, high-purity oxygen (purity ≥99.999%) is introduced into the furnace, and the pressure inside the furnace is maintained at 1.5 atmospheres (absolute pressure) through the pressure control system. Under this condition, the temperature is held for 0.5 hours to allow the oxygen to fully diffuse and penetrate into the interior of the green body. After the holding period, the oxygen supply is stopped and the gas inlet valve is closed. Then, the temperature is continued to rise at a rate of 2℃ / min to 1260℃, and held for 2 hours for densification sintering. During this process, as the temperature continues to rise, the gas inside the furnace expands due to heat, causing the pressure to rise naturally. The pressure inside the furnace is maintained at 1.5 atmospheres by controlling the flow rate at the gas outlet of the sintering furnace. After the holding period, the furnace is naturally cooled to room temperature to obtain high-performance Nb-PZT-based piezoelectric ceramics.
[0051] Example 2 introduces a 3 wt% excess PbO, which has the following three effects: First, the excess PbO forms a small amount of lead-rich liquid phase during high-temperature sintering. This liquid phase wets the grain boundaries and accelerates particle rearrangement and dissolution-precipitation mass transfer, significantly reducing the sintering activation energy and making the densification process more complete. Second, the lead-rich liquid phase fills the micropores at the grain boundaries, further improving the density and grain boundary bonding strength of the ceramic. Third, liquid-phase-assisted sintering further amplifies the effect of oxygen partial pressure: high oxygen partial pressure not only inhibits the continuous volatilization of PbO but also increases the chemical potential of oxygen in the liquid phase, allowing oxygen to diffuse more quickly into the lattice through the liquid phase channels, thereby more effectively reducing the bulk oxygen vacancy concentration. Therefore, referring to Table 2, in Example 2... d 33 The improvement (19.0%) is greater, which verifies that the method of the present invention has good compatibility and synergistic gain effect with other process means (such as PbO overcompensation), and can be flexibly combined according to different application requirements to further optimize the overall performance.
[0052] Table 2 lists a comparison of the performance tests of Nb-PZT piezoelectric ceramics sintered by oxygen partial pressure sintering and those sintered by air sintering.
[0053] Table 2: .
[0054] As shown in Table 2, in the Nb-PZT system with 3 wt% PbO excess, the oxygen partial pressure sintering process of this invention also achieves a comprehensive improvement in overall performance: piezoelectric coefficient d33 The pC / N ratio increased from 411 pC / N in air sintering to 489 pC / N, an increase of approximately 19.0%; the electromechanical coupling coefficient... k p and k t The efficiency of electrical energy to mechanical energy conversion was significantly enhanced, increasing from 0.67 and 0.57 to 0.74 and 0.61 respectively; Curie temperature... T C The temperature remained stable at 361 °C, indicating that oxygen partial pressure sintering did not alter the material's phase structure. The dielectric loss D decreased from 0.020 to 0.017, reflecting the optimizing effect of reduced oxygen vacancies on dielectric properties. The lead-rich liquid phase introduced by excess PbO promoted particle rearrangement and mass migration, and its synergistic effect with the high oxygen partial pressure suppressing volatilization resulted in a greater improvement in piezoelectric properties compared to the non-excess system in Example 1. d 33 (The improvement was 13.3%), which verified the technical advantages of combining liquid-phase assisted densification with oxygen partial pressure regulation. Example 3
[0055] In Example 3, high-performance BSPT-based piezoelectric ceramics (chemical composition 0.635PbTi) were prepared by controlling oxygen partial pressure based on shrinkage characteristics. 0.98 Hf 0.02 The sintering method for O3-0.365BiScO3 includes the following steps: (1) BSPT-based piezoelectric ceramic green bodies were prepared by solid-state method. Bi2O3, Sc2O3, Pb3O4, TiO2 and HfO2 were used as raw materials. The raw materials were weighed according to the stoichiometric ratio of BSPT-based piezoelectric ceramics. After mixing by planetary ball milling, drying and sieving, the raw materials were pre-fired at 850℃ for 2 hours to synthesize BSPT powder. The BSPT powder was ball-milled and granulated twice. It was first molded into a disc green body and then subjected to cold isostatic pressing to obtain BSPT green bodies. The pressure of cold isostatic pressing was 200 MPa and the holding time was 10 minutes. Then, the temperature was raised to 750℃ at a heating rate of 2℃ / min in air atmosphere and held for 2 hours to remove the granulating agent and organic binder. (2) Place the obtained BSPT green compact in an alumina crucible and then place it in a controlled atmosphere sintering furnace. Increase the temperature from room temperature to 600 ℃ (oxygen initiation temperature) at a heating rate of 2 ℃ / min. This temperature is determined based on the peak shrinkage rate of the BSPT green compact (e.g., ...). Figure 5As shown in the figure), when the temperature reaches 600℃, high-purity oxygen (purity ≥99.999%) is introduced into the furnace, and the pressure inside the furnace is maintained at 1.5 atmospheres (absolute pressure) through the pressure control system. Under this condition, the furnace is held for 0.5 hours to allow the oxygen to fully diffuse and penetrate into the interior of the green body. After the holding period, the oxygen supply is stopped and the gas inlet valve is closed. Then, the furnace is heated to 1180℃ at a heating rate of 2℃ / min and held for 3 hours for densification sintering. During this process, as the temperature continues to rise, the gas inside the furnace expands due to heat, causing the pressure to rise naturally. The pressure inside the furnace is maintained at 1.5 atmospheres by controlling the flow rate at the gas outlet of the sintering furnace. After the holding period, the furnace is allowed to cool naturally to room temperature to obtain high-performance BSPT-based piezoelectric ceramics.
[0056] Table 3 lists the performance test comparison of BSPT piezoelectric ceramics sintered by oxygen partial pressure sintering and those sintered by air sintering.
[0057] Table 3: .
[0058] As shown in Table 3, the oxygen partial pressure sintering method of this invention is also applicable to the BSPT high-temperature piezoelectric ceramic system, and the effect is significant: the relative density increases from about 94% in air sintering to about 98%, an increase of 4 percentage points. This indicates that the high oxygen partial pressure effectively suppresses the violent volatilization of Bi2O3 at high temperatures, avoids the obstruction of grain boundary migration caused by the formation of bismuth vacancies, and effectively eliminates closed pores under high-pressure oxygen atmosphere, achieving near-full densification; the piezoelectric coefficient... d 33 The performance improved from 340 pC / N to 363 pC / N, an increase of approximately 6.8%, although the BSPT system... d 33 While the absolute value is lower than that of the PZT system, it represents a significant improvement within the scope of high-temperature piezoelectric ceramics. It is noteworthy that the oxygen initiation temperature required for the BSPT system (600℃) is significantly lower than that for the PZT system (800℃). This is determined by the shrinkage characteristics of the BSPT green body itself—its sintering activity is higher, and its peak shrinkage rate temperature is lower. This also reflects that the volatilization initiation temperature of Bi₂O₃ is lower than that of PbO. Therefore, introducing a high oxygen partial pressure at a lower temperature is particularly important for this system. This embodiment verifies the broad applicability of the general strategy of determining the oxygen initiation temperature based on shrinkage characteristics in different piezoelectric ceramic systems, providing an effective technical path for the densification and performance optimization of high-temperature piezoelectric ceramics. Comparative Example 1
[0059] The sintering method of the Nb-doped Pb(Zr,Ti)O3 (Nb-PZT) based piezoelectric ceramic in Comparative Example 1 is the same as that in Example 1, except that the oxygen initiation temperature in step (2) is 950℃.
[0060] The performance test results of the Nb-PZT piezoelectric ceramic obtained in Comparative Example 1 are as follows: Piezoelectric coefficient d 33 The oxygen partial pressure sintering sample in Example 1 was 434 pC / N, which is lower than that in Example 1. d 33 =510 pC / N) significantly reduced, even lower than that of the conventional air-sintered sample in Example 1. d 33 Value (450 pC / N). Also from Figure 6 Scanning electron microscopy analysis of the cross-sectional morphology showed that the piezoelectric ceramic prepared in Comparative Example 1 exhibited obvious intergranular fracture characteristics, and the grain boundary bonding strength was significantly weaker than that of the sample in Example 1 that was oxygenated at 800°C. Comparative Example 2
[0061] The sintering method of the Nb-doped Pb(Zr,Ti)O3 (Nb-PZT) based piezoelectric ceramic in Comparative Example 2 is the same as that in Example 1, the only difference is that in step (2), oxygen sintering is carried out under normal pressure, that is, after high-purity oxygen is introduced, the pressure is not increased by the pressure control system, and the furnace is maintained at normal pressure (about 1 atmosphere) for oxygen sintering.
[0062] The performance test results of the Nb-PZT piezoelectric ceramic obtained in Comparative Example 2 are as follows: Piezoelectric coefficient d 33 It is 461 pC / N, which is higher than that of conventional air-sintered samples ( d 33 =450 pC / N) is an improvement, but significantly lower than the 1.5 atmosphere oxygen partial pressure sintered sample in Example 1 ( d 33 =510 pC / N). Simultaneously, by Figure 7 Scanning electron microscopy observation of the cross-sectional morphology showed that the piezoelectric ceramic prepared in Comparative Example 2 still had some residual pores in the cross-section, and the degree of density improvement was limited.
[0063] As can be seen from the above, although atmospheric pressure oxygen sintering inhibits PbO volatilization and reduces oxygen vacancy concentration to a certain extent, thus improving piezoelectric properties compared to air sintering ( d 33 The oxygen partial pressure inside the furnace was only 1 atmosphere, which limited the increase in oxygen partial pressure within the closed pores. This resulted in insufficient pressure difference between the inside and outside of the pores, weakening the driving force for pore contraction and preventing effective elimination of porosity. Simultaneously, the oxidation potential at atmospheric pressure was insufficient to reduce the oxygen vacancy concentration to a minimum, and residual defects still exerted a pinning effect on domain wall movement. Comparative Example 2 demonstrates the necessity of pressure control (1.5 atmospheres) in this invention—by moderately increasing the pressure, the pressure difference between the inside and outside of the closed pores is increased, accelerating oxygen diffusion and mass transfer and effectively eliminating porosity, while further reducing the oxygen vacancy concentration, achieving a significant improvement in density and piezoelectric properties.
[0064] The above description represents only some preferred embodiments of the present invention and is not intended to limit the invention in any other way. Any person skilled in the art may make changes or modifications to the disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention, without departing from the content and spirit of the present invention, shall still fall within the protection scope of the present invention.
Claims
1. A sintering method for high-performance piezoelectric ceramics based on oxygen partial pressure regulation using shrinkage characteristics, characterized in that, Includes the following steps: (1) Place the piezoelectric ceramic green body in a sintering furnace and heat it from room temperature to the oxygen initiation temperature at the first heating rate; (2) At the oxygen initiation temperature, high-purity oxygen is introduced into the sintering furnace, and the oxygen partial pressure in the furnace is controlled to the first oxygen partial pressure. The furnace is kept warm for the first preset time to allow the oxygen to fully diffuse and penetrate into the green body. After the heat preservation is completed, the oxygen supply is stopped and the gas inlet valve is closed. (3) Continue heating at the second heating rate to the sintering temperature and hold for the second preset time to make the green billet densify and sinter; during this process, as the temperature inside the furnace continues to rise, the gas inside the furnace expands due to heat and the pressure naturally rises, and the first oxygen partial pressure is maintained by controlling the flow rate at the gas outlet of the sintering furnace. (4) After the heat preservation in step (3) is completed, the furnace is cooled to room temperature to obtain the high-performance piezoelectric ceramic.
2. The sintering method according to claim 1, characterized in that, In step (1), the piezoelectric ceramic is selected from Pb(Zr,Ti)O3-based piezoelectric ceramics (PZT), bismuth-based perovskite (BSPT)-based piezoelectric ceramics or bismuth layered structure (BLSF) piezoelectric ceramics; The preparation method of the piezoelectric ceramic green body includes: weighing raw materials according to the stoichiometric ratio of piezoelectric ceramics, mixing them by planetary ball milling, drying them, sieving them, and then pre-firing them to synthesize piezoelectric ceramic powder; After the piezoelectric ceramic powder is ball-milled and granulated twice, it is first molded and then subjected to cold isostatic pressing to obtain the piezoelectric ceramic green body; preferably, the pressure of the cold isostatic pressing is 150-300 MPa and the holding time is 1-10 minutes.
3. The sintering method according to claim 1 or 2, characterized in that, In step (1), the first heating rate is 2 to 5 °C / min.
4. The sintering method according to any one of claims 1-3, characterized in that, In step (1), the oxygen initiation temperature is determined by the following method: performing a shrinkage curve test on the piezoelectric ceramic green body to obtain the shrinkage rate curve of the green body during the heating process, and taking the temperature corresponding to the start of shrinkage as the oxygen initiation temperature; preferably, the oxygen initiation temperature is 600-850 ℃.
5. The sintering method according to any one of claims 1-4, characterized in that, In step (2), the purity of the high-purity oxygen is ≥90%, preferably ≥99%; The pressure of the first oxygen partial pressure is 1.2 to 2 atmospheres; The first preset time is 0.5 to 1 hour.
6. The sintering method according to any one of claims 1-5, characterized in that, In step (3), the second heating rate is 1-2 °C / min; The sintering temperature is 1100–1280 °C; Preferably, when the piezoelectric ceramic is a PZT system, the sintering temperature is 1200–1280 °C; Preferably, when the piezoelectric ceramic is a BSPT system, the sintering temperature is 1150–1250 °C; Preferably, when the piezoelectric ceramic is a BLSF system, the sintering temperature is 1100–1200 °C.
7. The sintering method according to any one of claims 1-6, characterized in that, In step (3), the second preset time is 1 to 4 hours.
8. The sintering method according to any one of claims 1-7, characterized in that, In step (4), the cooling rate is 2 to 5 °C / min.
9. A high-performance piezoelectric ceramic prepared by the sintering method according to any one of claims 1-8.
10. The high-performance piezoelectric ceramic according to claim 9, characterized in that, The relative density of the high-performance piezoelectric ceramic is ≥98%; The high-performance piezoelectric ceramic has a piezoelectric coefficient d. 33 It improves upon traditional air sintering by more than 6%; When the piezoelectric ceramic is a PZT system, the Curie temperature is ~360 ℃; When the piezoelectric ceramic is a BSPT system, the Curie temperature is ~450 ℃; When the piezoelectric ceramic is a BLSF system, the Curie temperature is ~650 ℃.